2018
DOI: 10.15804/tner.2018.53.3.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incentive Reward, School Principal Leadership, Work Motivation on the Performance of Senior High School Teachers in Medan

Abstract: Improving teaching performance is most likely an act that leads to substantial gains in student learning, essential to know the strengths of teachers and those aspects of their practice which could be further developed. Th e objective of this research is to fi nd out the eff ect of incentive, leadership, and work motivation on teacher performance. Research fi ndings showed a direct eff ect of incentive reward on teacher performance, which reached the value of 0.350, whereas the indirect eff ect of incentive on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Pancasila et al ( 76 ) showed that work motivation positively affected work performance (Direct effect: 0.17). Nasution ( 77 ) suggested that incentive remuneration positively affected teacher continuous improvement (Direct effect: 0.35). Fuller and Harding ( 78 ) and Hersona and Sidharta ( 79 ) also demonstrated this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pancasila et al ( 76 ) showed that work motivation positively affected work performance (Direct effect: 0.17). Nasution ( 77 ) suggested that incentive remuneration positively affected teacher continuous improvement (Direct effect: 0.35). Fuller and Harding ( 78 ) and Hersona and Sidharta ( 79 ) also demonstrated this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of them are of US origin, professional periodicals have published a considerable number of studies from various European and Asian countries. The first research has focused on characteristics of school leaders, principals, and later attention has turned to leadership behaviour of principals and teachers and to the impact of leadership on pupils' academic achievements (e. g. Purkey & Smith, 1983;Riehl & Firestone, 2005) or teachers' achievements (Aydin, Sarier & Uysal, 2013;Nasution, 2018;Zare & Nastiezaie, 2019). Numerous research has confirmed that teachers' leadership has a positive effect on pupils' outcomes, on achieving the vision of the school, on the school climate, that the teacher leader can positively influence pupils' involvement in classes (Silins & Mulford, 2004), students' achievements (Goddard, Hoy & Hoy, 2000), etc.…”
Section: Problem Of Researchmentioning
confidence: 99%